PENGARUH MINUMAN REMPAH JAHE ASAM TERHADAP PENURUNAN SKALA NYERI HAID PRIMER PADA REMAJA - Sugiharti, Rosi Kurnia; Sukmaningtyas, Wilis (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Puberty is a transitional period between childhood and adulthood where growth spurt occurs. At this time many changes both psychologically and biologically one of them is dysmenorrhea. The purpose of this study to determine the effect of acid ginger spice on decreasing the scale of primary menstrual pain in female midwifery students D3 STIKES Harapan Bangsa Purwokerto. The research model used is quasi experiment because the requirements in the experimental research is not sufficient that is not doing the control of the variables that affect the experiment. The design of this study is one group pre and post test design that is by using one group of respondents in which the group is given Sample treatment by using purposive sampling. The results of this study are scientific publications and textbooks on reproductive health. The result of the research shows that p value = 0.0001 which means <Î± 0,05 which concludes that Ha is accepted and Ho is rejected. This shows that there is the influence of acid ginger spice drink to decrease the scale of primary menstrual pain. Keywords: Influence, Acid Ginger Spice Drink, Primary Menstrual Pain Scale